Supporting Factors of Student Exchange Programs: An Analysis of Students’ Perceptions - Supriyanto, S; Roesminingsih, Erny; Nuphanudin, N; Wulandari, Ayu; Muhimmah, Hitta Alfi; Wibowo, Amiruddin Hadi; Sabariah, S; Hisham, Ts. Syariffanor binti (Studies in Learning and Teaching, 2025)
This study describes the perceptions of outbound and inbound students about various supporting factors of the student exchange program at Universitas Negeri Surabaya. This study used an evaluation research design with a descriptive quantitative approach. Data were collected through a questionnaire and analyzed using descriptive statistics. The results show that most respondents said pre-departure communication and support from the university were good or very good. Students also felt ready to join the program, helped by their own motivation and support from their families. They thought it was good that they could take different courses and get cross-credit. However, there were still some problems with adjusting the curriculum. The collaborative learning process and active participation in seminars and workshops strengthen the student learning experience. In addition, the level of tolerance and social acceptance between exchange program students and regular students is very high. This study provides a comprehensive empirical picture of the implementation of the student exchange program and can be a reference for developing more inclusive and adaptive policies in higher education.